Psychometric Evaluation of the Thai Version of the Burdened Caregiver Scale for Schizophrenia and Co-occurring Methamphetamine Use: A Pilot Study [version 4; peer review: 1 approved, 2 approved with reservations] - Ek-uma Imkome (F1000Research)
Objective To develop and test the psychometric properties of the Thai version of the Impact and Burden of Care Scale for Caregivers of Persons with Schizophrenia and Co-occurring Methamphetamine Use (TIBSCSM). Methods This pilot study involved 142 caregivers of individuals with schizophrenia and methamphetamine use. Sample adequacy was assessed using the Kaiser–Meyer–Olkin (KMO) method, while Bartlett’s test evaluated the item correlation matrix. Exploratory factor analysis (EFA) was conducted to identify underlying factors. Results The 32-item TIBSCSM showed convergent validity correlations with two quality-of-life measures. The KMO value was 0.90, and Bartlett’s Test of Sphericity yielded χ2 = 5248.5, df = 496, p < 0.001. The Content Validity Index (CVI) was 1, indicating high internal consistency reliability (α = 0.90). EFA identified four constructs: physical function, self-esteem, role and social enjoyment, and relationship satisfaction. The model exhibited strong reliability and validity, with an average variance extracted (AVE) of 0.948 and composite reliability (CR) of 0.987, accounting for 64.90% of the variance. Conclusion The TIBSCSM scale provides valuable insights for psychiatric nurses and mental health teams to measure the impact and burden experienced by caregivers of individuals with schizophrenia and methamphetamine use. It is particularly useful for nursing, research, education, and clinical practice, especially in addressing the caregiver burdens exacerbated during the COVID-19 pandemic. Implication for nursing and research The TIBSCSM, developed in the Thai context, can facilitate studies evaluating variations in caregiver impact across different settings.